Culture and Development in a Globalizing World - Radcliffe, Sarah (Taylor & Francis, 2006)
Using recent research on development projects around the world, this book argues that culture has become an explicit tool and framework for development discourse and practice. Providing a theoretical and empirically informed critique, this informative book includes conceptual overviews and case studies on topics such as: development for indigenous people natural resource management social capital and global markets for Third World music post-apartheid South Africa cultural difference in the USA's late capitalism. The editor concludes by evaluating the outcomes of development's 'cultural turn', proposing a framework for future work in this field. By combining case studies from both 'Third World' and 'First World' countries, the book, ideal for those in the fields of geography, culture and development studies, raises innovative questions about the 'transferability' of notions of culture across the world, and the types of actors involved.